Early childhood feeding practices and its association with early childhood caries - Rusali, Roszanadia; Hamali, Nur Najwa; Muhammad Razi, Fadhilah; Mustafa, Norashikin; Harun, Nor Asilah; Mohd Shukri, Nor Azwani (Science and Education Publishing Co. Ltd, 2019)
Early childhood caries (ECC) is one of the most prevalent dental diseases among children and is related to their early feeding practices. This multi-factorial disease involves susceptible tooth and host, fermentable carbohydrates in the diet, cariogenic micro-organisms and time (American Academy of Pediatric Dentistry, 2008). Thus, this study aimed to identify the associations between bottle-feeding and weaning practices, and ECC formation. By using convenience sampling, 201 children were recruited from the IIUM Outpatient Dental Clinic and ten kindergartens around the area of Kuantan, in the state of Pahang (Malaysia). Examination for caries was conducted visually to determine caries status (with or without caries). The caregivers were requested to fill in a questionnaire regarding feeding practices of their children. The findings of the study indicated that 67% of the children identified with caries practiced bottle-feeding in bed either sometimes or always (every night/day) (p=0.005). The prevalence of ECC was also significantly (p<0.001) the highest (48.5%) among children who had been bottle-feeding for the longest duration (>4 years) among the study population. In addition, the mean intake of sweetened drinks among children with ECC was significantly higher than those with no ECC (5.4 vs. 3.1 servings/week, p=0.001). The results of this research indicated that the increased frequency and prolonged duration of bottle-feeding practices, as well as high consumption of sweet drinks during weaning, could be associated with the formation of ECC. In conclusion, these findings would increase the awareness particularly among parents regarding bottle-feeding practices and weaning diet contents and its potential implication on their children’s oral health.